Scientific explanation of e+ and Weyl fermion for injecting semiconductor devices - Abbas, Arwa Saud (Frontiers in Electronics, 2025)
The scientific explanation of utilizing the positron and Weyl fermion in semiconductors is presented. In view of the slow e+ beam-generation development for imaging technology alongside the Weyl fermion which carries charge like an electron, but has no mass, thus moves much faster, injecting semiconductor devices is addressed. The information gained from this prediction has allowed the broadening of its implementation to semiconductor technology with electronic excitation using sources other than e-. Developing the positron microbeam and Weyl fermions can be described with the concept of type I positron beam source is an alternative source of electron beam, thus harnessing the generation of γ-ray radiations inside the semiconductor heterostructures with indicating e+ and e− interaction with materials are different and type II Weyl fermions. Thus, the properties of positrons and Weyl fermion are considered suitable for carrier transport in optoelectronics. Perspectives of the development of alternative beam source for super-transport are provided.